The Influence of Environmental Education and Community Discipline on Lake Toba Environmental Sustainability Concern in Samosir Regency - HD. Melva Sitanggang*; Togu Harlen Lbn. Raja; Edward A. Lbn. Raja (Universitas Syiah Kuala, 2023)
The earth, water and air contained in it are all natural resources that can be managed properly so that they can be used to meet the needs of people's lives so that the environment must be preserved. Lake Toba is one of the natural resources in Indonesia and there are several districts around Lake Toba where one of them is Samosir Regency which is on Samosir Island and surrounded by Lake Toba. The beauty of Lake Toba can be used as a source of income for the community and the area of Samosir Regency so that the environment must be preserved through environmental education and community discipline. As respondents in this study were the people around the tourist area in Samosir Regency who were taken randomly as many as 60 people. The results of the study explain that environmental education has an effect on concern for the environmental sustainability of Lake Toba by 16.63%, community discipline has an effect on concern for the environmental sustainability of Lake Toba by 23.76% and together that environmental education and community discipline have an effect on concern for the environmental sustainability of Lake Toba. Tioba by 45.37%.